Completion of the audit cycle: standardised nurse-led information for patients. Issue 937 (3rd December 2003) - Sharma, R A; Furber, L; Granger, L D; Archdeacon, C; Thomas, G; Symonds, R P
Abstract : Background:: It is increasingly accepted that patients want information about their proposed treatment, and that provision of such information may alleviate fear and may improve the process of obtaining informed consent. It is not yet clear what form such information should take. Objective:: Based on differences shown previously between patients receiving standard treatment and those in clinical trials, a system of routine appointments with a chemotherapy nurse at least one day before the patient offered consent to treatment was established for all patients receiving chemotherapy in Leicestershire, at which time patients were given standardised written information regarding outpatient chemotherapy and specific drugs. Method:: In order to complete the audit cycle, the previous questionnaire study was repeated. Results:: From 160 questionnaires distributed, 131 complete replies were received. Compared with the previous audit, a significantly higher proportion of patients receiving standard chemotherapy remembered being given written information about chemotherapy from a nurse before starting their treatment and remembered signing a consent form. The significant difference in feelings of involvement in the decision to have chemotherapy between patients receiving standard chemotherapy and those in clinical trials detected in the previous audit was no longer detectable, suggesting the clinical effectiveness of the intervention performed. Conclusion:: Implementation of nurse-led appointments with provision of standardised information before formal consent being taken should be studied further for its potential to improve patients' involvement in medical decision making.